Memasyarakatkan Tanya 5O Dan Efek Interaksi Obat Pada Siswa MTsN 2 Kota Palangka Raya: Promoting “Tanya 5 O” and Effects of Drugs on Nutritional Status in Students of MTsN 2 Palangka Raya - Harlyanti Muthma'innah Mashar; Normila Normila; Juni Ramadhani; Dali Dali; Ismail Ismail (Progran Studi Farmasi STIKES Mandala Waluya, 2021)
This community service is a form of sharing program of cooperation from the Ministry of Health of the Republic of Indonesia and the Provincial and City Health Offices, namely GeMa CerMat (Smart Community Movement Using Drugs), one of which is through the promotion of the tagline